IMPLEMENTASI METODE ANABA DALAM PEMBELAJARAN AL-QUR'AN: STUDI PENGAJIAN LANSIA DI PAJANG SURAKARTA - Winda Angan Sari; S Syamsuddin; Indah Nur Hidayati (Al'Ulum Jurnal Pendidikan Islam, 2021)
The purpose of this study was to determine the implementation of the Anaba method in studying the Qur'an for the elderly at the Pajang Pajang Surakarta. This research is a qualitativeresearch with the subject of the study of the Elderly Study in Pajang Surakarta. Data were taken using observation, interviews and documentation. Meanwhile, data analysis is done by data reduction, data display and data verification. The results of this study indicate that the characteristics of elderly mothers. The study at Pajang is very pleasant and full of ukhuwah Islamiah, so it is easy to create a relaxed learning atmosphere, not tense, and without coercion from anyone. They have different levels of understanding, some are fast and some are slow in accepting the learning of the Qur'an. Then the implementation of the very practical and efficient Anaba method was proven to improve the ability to read the Qur'an of the elderly at the Pajang Pajang Surakarta.